Photosensitized Thermoplastic Nano-Photocatalysts Active in the Visible Light Range for Potential Applications Inside Extraterrestrial Facilities - Lidia Mezzina; Angelo Nicosia; Fabiana Vento; Guido De Guidi; Placido Giuseppe Mineo (Nanomaterials, 2022)
Among different depollution methods, photocatalysis activated by solar light is promising for terrestrial outdoor applications. However, its use in underground structures and/or microgravity environments (e.g., extraterrestrial structures) is forbidden. In these cases, there are issues related to the energy emitted from the indoor lighting system because it is not high enough to promote the photocatalytic mechanism. Moreover, microgravity does not allow the recovery of the photocatalytic slurry from the depolluted solution. In this work, the synthesis of a filmable nanocomposite based on semiconductor nanoparticles supported by photosensitized copolyacrylates was performed through a bulk in situ radical copolymerization involving a photosensitizer macromonomer. The macromonomer and the nanocomposites were characterized through UV-Vis, fluorescence and NMR spectroscopies, gel permeation chromatography and thermogravimetric analysis. The photocatalytic activity of the sensitized nanocomposites was studied through photodegradation tests of common dyes and recalcitrant xenobiotic pollutants, employing UV-Vis and visible range (λ > 390 nm) light radiations. The sensitized nanocomposite photocatalytic performances increased about two times that of the unsensitized nanocomposite and that of visible range light radiation alone (>390 nm). The experimental data have shown that these new systems, applied as thin films, have the potential for use in indoor deep underground and extraterrestrial structures.